تأثير ضغط الانتفاخ على الخصائص الفيزيائية و الميكانيكية لبعض الترب الغضارية الساحلية(قدرة التحمل في حالة الجدران الاستنادية) - فياض توفيق (Latakia University Journal -Engineering Sciences Series, 2016)
تؤسَّس أغلب المنشآت المنفذة و قيد التنفيذ في سوريا على ترب غضارية أو غضارية سيلتية تتصف بقابليتها للانتفاخ، و هو ما يجعل المنشآت المبنية عليها معرضةً لتشوهات تختلف بحجمها و شكلها و تأثيرها تبعاً لضغط الانتفاخ المسجل عليها. تتراوح هذه التشوهات بين التشققات البسيطة و الشقوق المتقدمة التي قد تؤثر سلباً على استثمار المبنى. تبدو هنا الحاجة ملحةً لتقديم دراسة كافية لخصائص هذه الترب للوقوف على التأثير المباشر و غير المباشر للانتفاخ على خصائص التربة من جهة، و سلوك المنشآت المبنية عليها من جهة أخرى. حاولنا في هذا البحث دراسة تأثير انتفاخ التربة الغضارية على خصائصها الفيزيائية و الميكانيكية من حيث انخفاض قيم زاوية الاحتكاك الداخلية  ، و قيم التماسك c ، و بالتالي انخفاض قدرة التحمل لهذه التربة الذي سيفرض بدوره قيماً أكبر لأبعاد الأساسات المصممة. يظهر ذلك بوضوح على النماذج الثلاث من التربة الغضارية المستخرجة من مواقع مختلفة في المنطقة الساحلية، و التي أجريت عليها اختبارات التشديد للوقوف على قيم معامل الانتفاخ و ضغط الانتفاخ، و اختبارات القص المباشر و تحديد الكثافات لحساب قدرة التحمل و مقارنتها مع ترب تختلف معها بقيم معامل الانتفاخ. Establishing and executing most of the installations under construction in Syria on soils Clays or Clays Sillete characterized by its propensity to bulge, and is what makes them vulnerable installations built to deformities vary in size and shape and influence depending on the swelling pressure recorded them. These range from simple distortions between the cracks and crevices developed which may adversely affect the investment of the building. Look here is an urgent need to provide sufficient study of the properties of these soils to determine the effect of direct and indirect bulge on the characteristics of the soil on the one hand, and the behavior of structures built by the other hand In this research, we tried to study the effect of swelling soils conflment on their physical properties and mechanical values in terms of reduced internal friction angle , and the values of cohesion c, and thus lower carrying capacity of these soils, which in turn would impose more valuable to the dimensions of the foundations designed. Clearly shown on the models of the three soil conflment extracted from different locations in the coastal region, and which have been tested to stress to determine the values of coefficient of swelling and swelling pressure, and shear tests direct and determine densities to calculate the endurance and compared with soils vary with the values of coefficient bulge.